Pengujian Eksperimental Panas Yang Timbul Akibat Gesekan Pada Kampas Rem Cakram Komposit Berbahan Serat Rami Dan Serbuk Arang Tempurung Kelapa Dengan Perekat Resin Epoksi - Kusmardin, Kusmardin; Mangalla, Lukas Kano; Samhuddin, Samhuddin (Teknik Mesin Universitas Halu Oleo, 2019)
The purpose of this study was to determine the heat that builds up and the rate of abrasion due to friction on the brake discs made of fiber composite jute, coconut shell with an epoxy resin adhesive. The tools used in this study are digital thermometer, abrasion, stopwatch, thermometer, digital scales while the materials used are ramie fibers, coconut shell charcoal, and epoxy resin. Comparison of a mixture of ramie fiber, coconut shell powder, and epoxy resin namely for canvas 1 (30:30:40 %), canvas 2 (20:40:40 %), and (40:20:40 %). The lowest abrasion rate value in the 3rd sample with a composition (40 % ramie fiber, coconut shell charcoal powder 20 %, and 40 % epoxy resin) is 0,00071 gr/ s, the thermal conductivity value of the material drops at 30 % ramie content and increases in the 40 % content of ramie.Keywords: brake lining, abrasion rate, thermal conductivity, ramie and epoxy